Melancholy of the misconstrued mining machine - Ludick, Devan (University of the Free State, 2020)
The existence of architecture that evokes defining moments of possibilities where its users are able to transcend the unseen tying threads of the system. Moments that create a new awareness to the narrative presented; the overarching segmented mining history of South Africa. Divulging the tragic and sanguine realities surrounding this controversial field, by exposing the tension that exists between mines, miners and the fragility of its support systems. Focusing on singular prominent examples throughout history, to convey a narrative by means of structure and spatial experiences. Leaving the conclusion of the narrative to the user. In hopes to help develop a better society by revealing truths and providing a home for initiatives that support objectives surrounding mine communities, polluted landscapes and sustainable new methods in these areas.
Dissertation (M.Arch. (Architecture))--University of the Free State, 2020
Keywords: Mining machinery industry; Mineral industries; Mines and mining - South Africa - History; Architecture